USE OF ETANERCEPT IN PATIENTS WITH OLIGOARTICULAR JUVENILE IDIOPATHIC ARTHRITIS - Т. М. Bzarova; Ye. I. Alekseeva; О. L. Lomakina; K. B. Isaeva; S. I. Valieva; R. V. Denisova; Т. V. Sleptsova (Вопросы современной педиатрии)
The article describes a case of torpid course of oligoarticular juvenile idiopathic arthritis (JIA) and the successful use of soluble receptorsf or tumor necrosis factor alpha (TNF) — etanercept — during its treatment. After 4 weeks of treatment the patient returned to normal laboratory indices of the disease activity, and the duration of morning stiffness and severity of inflammatory changes in the joints decreased; after 3 months the acute inflammatory changes in the joints disappeared; after 6 months the patient's functional ability restored; and after 9 months the medically induced remission of the disease was recorded.